Temperature differences between sites lead to altered phenylpropanoid metabolism in a varietal dependent manner - Gashu, Kelem; Verma, Pankaj Kumar; Acuña, Tania; Agam, Nurit; Bustan, Amnon; Fait, Aaron (Frontiers in Plant Science, 2023)
Elevated temperature has already caused a significant loss of wine growing areas and resulted in inferior fruit quality, particularly in arid and semi-arid regions. The existence of broad genetic diversity in V. vinifera is key in adapting viticulture to climate change; however, a lack of understanding on the variability in berry metabolic response to climate change remains a major challenge to build ad-hoc strategies for quality fruit production. In the present study, we examined the impact of a consistent temperature difference between two vineyards on polyphenol metabolism in the berries of 20 red Vitis vinifera cultivars across three consecutive seasons (2017)(2018)(2019). The results emphasize a varietal specific response in the content of several phenylpropanoid metabolites; the interaction factor between the variety and the vineyard location was also found significant. Higher seasonal temperatures were coupled with lower flavonol and anthocyanin contents, but such reductions were not related with the level of expression of phenylpropanoid related genes. Hierarchical clustering analyses of the metabolic data revealed varieties with a location specific response, outstanding among them was Tempranillo, suggesting a greater susceptibility to temperature of this cultivar. To conclude, our results indicate that the extensive genetic capacity of V. vinifera bears a significant potential to withstand temperature increase associated with climate change.